Universality of the Triangular Theory of Love: Adaptation and Psychometric Properties of the Triangular Love Scale in 25 Countries. Issue 1 (2nd January 2021) - Sorokowski, Piotr; Sorokowska, Agnieszka; Karwowski, Maciej; Groyecka, Agata; Aavik, Toivo; Akello, Grace; Alm, Charlotte; Amjad, Naumana; Anjum, Afifa; Asao, Kelly; Atama, Chiemezie S.; Atamtürk Duyar, Derya; et al.
ABSTRACT: The Triangular Theory of Love (measured with Sternberg's Triangular Love Scale – STLS) is a prominent theoretical concept in empirical research on love. To expand the culturally homogeneous body of previous psychometric research regarding the STLS, we conducted a large-scale cross-cultural study with the use of this scale. In total, we examined more than 11, 000 respondents, but as a result of applied exclusion criteria, the final analyses were based on a sample of 7332 participants from 25 countries (from all inhabited continents). We tested configural invariance, metric invariance, and scalar invariance, all of which confirmed the cultural universality of the theoretical construct of love analyzed in our study. We also observed that levels of love components differ depending on relationship duration, following the dynamics suggested in the Triangular Theory of Love. Supplementary files with all our data, including results on love intensity across different countries along with STLS versions adapted in a few dozen languages, will further enable more extensive research on the Triangular Theory of Love.